Peran Mediasi Motivasi Kerja Pada Pengaruh Komitmen Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara - Nelson Pardamean (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to examine and analyze the effect of organizational commitment and work environment on employee performance mediated by work motivation at the Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara directly or indirectly. The approach used in this study is a causal approach. The population in this study were all state civil servants at the Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara. The sample in this study used a sample of the slovin formula totaling 67 state civil servants at the Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly organizational commitment, work environment and work motivation have a significant effect on employee performance and indirectly work motivation is able to mediate the significant influence of organizational commitment and work environment on employee performance at the Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara.